2020
DOI: 10.1016/j.ribaf.2020.101200
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Efficiency and Arbitrage in the Bitcoin Spot and Futures Markets

Abstract: This study examines the pricing efficiency for the leading cryptocurrency, Bitcoin using spot prices and all CBOE and CME futures contracts traded from January 2018 to March 2019. We find that the futures basis provide some predictive power for future changes in the spot price and in the risk premium. However, the basis of Bitcoin is a biased predictor of the future spot price changes. Cointegration tests also demonstrate that futures prices are biased predictors of spot prices. Deviations from no-arbitrage be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Based on the fact the Bitcoin market became a common financial market, researchers also investigated on the issue PLOS ONE of whether Bitcoin market was predictable. Despite Urquhart [21] argued the weak form efficiency, numerous studies found empirical evidence on the predictability of Bitcoin return from several aspects, i.e., trading volume, exchange rates, mining rate, revenue, as well as several market indexes [45][46][47][48][49][50][51][52][53][54], etc. Based on the time-varying long memory properties in Bitcoin market, Bariviera et al [55] investigated the Bitcoin volatility forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the fact the Bitcoin market became a common financial market, researchers also investigated on the issue PLOS ONE of whether Bitcoin market was predictable. Despite Urquhart [21] argued the weak form efficiency, numerous studies found empirical evidence on the predictability of Bitcoin return from several aspects, i.e., trading volume, exchange rates, mining rate, revenue, as well as several market indexes [45][46][47][48][49][50][51][52][53][54], etc. Based on the time-varying long memory properties in Bitcoin market, Bariviera et al [55] investigated the Bitcoin volatility forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It should be noted that the cryptocurrency market is tightly interdependent to commodity markets (Ji et al, 2019;Panagiotidis et al, 2019), derivative markets (Akyildirim et al, 2020), bond and foreign exchange markets (Corbet et al, 2018). Furthermore, Bitcoin COVID-19 pandemic futures have been traded in Chicago Mercantile Exchange and the Chicago Board Options Exchange since December 2017 and these innovative products have raised interest by investors (Lee et al, 2020). Thus, a shock stemmed in the cryptocurrency market can spread to the financial markets with its detrimental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Among these papers, find that BitMEX perpetual swaps lead prices on major bitcoin spot exchanges indicating its strong price discovery and higher informational efficiency. Unlike existing studies, Lee et al (2020) examine the markets in terms of arbitrage efficiency and find that futures prices are biased predictors of future spot prices. Entrop et al (2020) go one step further and investigate the factors that may impact bitcoin price discovery in both spot and futures markets and find a significant time-variation in their contribution to price discovery of both markets.…”
Section: Introductionmentioning
confidence: 94%